Kajian Komparatif Materi Darah Perempuan Pada Buku Teks (PAI BP) dan Buku Fikih Kelas 4 SD Dan MI - Badriyah, Lailatul; Atiqullah, Atiqullah; Sa’diyah, Halimatus; Rokib, Moh (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Textbooks serve as primary learning resources in schools and are expected to provide accurate, structured, and comprehensive material. This study aims to conduct a comparative analysis of the presentation of female blood material in the Islamic Religious Education and Ethics (PAI BP) textbook for grade 4 students at SD Negeri Tanjung 5 and the grade 4 fiqh textbook at MI Negeri 1 Pamekasan. Specifically, the research seeks to examine (1) the presentation of female blood material in both textbooks, (2) the similarities and differences in their content, and (3) the extent to which the formulation of the material meets students’ learning needs. This research employed a qualitative approach with library research as its design. Data were collected through documentation of primary sources PAI BP textbook (2021) and fiqh textbook (2023), as well as secondary sources from relevant literature. The data were analyzed using content analysis. The findings indicate that the fiqh textbook provides more detailed coverage, particularly on menstruation, including its definition, characteristics, duration, restrictions, and obligatory bathing, while also briefly addressing istihadhah and nifas. In contrast, the PAI BP textbook limits its discussion to menstruation, adopting a narrative and integrative approach that combines fiqh and biological perspectives. Both books share similarities in positioning menstruation within the puberty chapter but differ in depth, argumentation, and evaluation techniques, with fiqh offering broader conceptual-theoretical content than the more contextual narrative of PAI BP.